Teaching & learning inquiry - International Society for the Scholarship of Teaching and Learning (Bloomington, IN : Indiana University Press, 2013)
Aims to feature original research and commentary on the scholarship of teaching and learning in higher education.
Description based on Vol. 1, issue 1 (2013); title from PDF running title (Project Muse, viewed Apr. 23, 2013).
Latest issue consulted: Vol. 4, No. 1 (2016) (tlijournal.com viewed May 3, 2016).
Keywords: Learning and scholarship -- Periodicals; Postsecondary education -- Research -- Periodicals; College teaching -- Research -- Periodicals; Education, Higher -- Periodicals; College teaching -- Research; Education, Higher; Learning and scholarship; Electronic journals